Dataset of Soil Hydraulic Parameters in the Yellow River Basin - Yongping Tong; Yunqiang Wang; Jingxiong Zhou; Xiangyu Guo; Ting Wang; Yuting Xu; Hui Sun; Pingping Zhang; Zimin Li; Ronny Lauerwald (PANGAEA, 2024)
Soil hydraulic parameters are vital for precise characterization of soil hydrological processes. Although many studies have integrated comprehensive soil datasets, availability of data in sufficient quality remains limitted, especially for deep soil information from in-situ measurement. This dataset contains soil hydraulic parameter data, including 2924 soil texture, 2798 bulk density (BD), 2782 saturated hydraulic conductivity (Ks), and 1035 soil water retention curve (SWRC) parameter records down to a maximum profile depth of 5 m. It encompasses the entire Yellow River Basin (795,000 km^2) which ranking as the fifth longest river in the world. Soil samples were obtained using high-density in situ field sampling at 475 sites from 2008 to 2019. The soil texture, BD, and Ks were directly measured from field samples. Mastersizer laser particle size analysers (Mastersizer 3000, Malvern Panalytical, UK) were used to determine soil particle size distribution and the classification of soil texture followed USDA standards. The undisturbed soil samples were initially immersed for 24 h to achieve full saturation, before we performed the determination of Ks using the constant-head method. The SWRC were measured by centrifuge (CR21N, Hitachi, Japan) first and we then used soilhypfit package in R (4.2.3) to predict SWRC parameters. The BD was assessed by oven-drying method (at 105°C for 10 h). All data underwent quality checks, and the dataset includes detailed annotations regarding the testing methods and data quality for various parameters.